Seed Morphology and Dispersal Features of Euphorbia hypericifolia L. (Euphorbiaceae) from a New Distributional Area in Benghazi, Libya - Abdelbsit M. Asker; Salem El Shatshat; Salem A. Hassan; Mabroukha K. AlfakhriAria; Enas M. Albarasi (African Journal of Advanced Pure and Applied Sciences, 2025)
This study documents a new distribution record for Euphorbia hypericifolia L. (Euphorbiaceae) in Benghazi, Libya. Plant specimens were collected from three different locations: Al-Fuwaiha, Jamal Abdel Nasser Street, and Bu Snieb. Morphometric analysis showed that the seeds, which are broadly elliptic to elliptic, have average dimensions of 0.715 mm in length and 0.496 mm in width. This results in an average length/width (L/W) ratio of 1.447. Their surface is slightly wrinkled or transversely furrowed, with shallow, irregular transverse ribs. The research confirms that the species uses Ballochory (explosive dispersal) through the three-lobed capsule (regma) as its main method for distribution. But it isn’t the main reason for its effective spread across Eastern Libya. One-Way Analysis of Variance (ANOVA) found that the mean seed length and L/W Ratio were not statistically significant among the three locations, confirming the overall morphometric stability of the seed structure. However, the analysis showed a significant difference in the mean Capsule Length among the three sites (F = 4.3164, P=0.0232). This data enhances our understanding of the species distribution, grwoth patterns and serves as an important basis for updating plant records in Libya.